Semantic Negation on Verbal Clauses with Verbs of Imminence in Saudi Arabic Varieties - Salih Alzahrani (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
Negation in languages is a phenomenon, which receives researchers' attention for a long period. Negation occurs on different type of clauses by which it shows to have morphological and syntactic changes over the structure of words, phrases and sentences. Verbs of imminenceare used sometimes to denote negation in verbal clauses in Arabic. ka:d  is one of those verbs which carries the negation of the clause without using any negative particles. Saudi dialects use the verb baʁa to perform the same function. This paper discusses baʁa in verbal clauses illustrating its syntactic and semantic impact on the structure of the clauses. It requires the imperfective form of the verb to follow. Negating a clause, with the only negative particles ma: and/or la:, does not carry the negative sense because it is delivered through the use of baʁa. Thus, the negation of verbs of imminence does not require the presence of any negative particles. Otherwise, the positive meaning is delivered.